Subliminal Messages in Comic Books: A Semiology Study on Ardian Syaf’s Case - Yudhy Setyo Purwanto (Humaniora, 2018)
The research aimed at knowing the meaning behind the symbols and messages, both the signifier and the signified which in the end could reveal the meta-language meaning. This research used Semiology approach to analyze the images inside the panels of the comic book of Ardian Syaf’s the ‘X-Men Gold vol.1: Back to the Basics. The qualitative method of Semiology could successfully explain the media phenomena. The approach was mostly leaned on Barthes’ work on new Semiology doctrine which enables the researchers to figure out and prove that the non-verbal communication could have a wide interpretation of some significance meanings. The result of the study indicates that (1) all of the messages are related to the 212 event and Al-Maidah 51, (2) the messages portray the relation between Moslems, Jews, and Christians in the artist’s perspective; and (3) all of the messages, thoughthey have a bigger agenda, are related to one character, Kitty Pryde.